Analysis of Educators’ Work Motivation in Supporting Main Tasks of Development and Education Command of Indonesian Navy (Causal Study in Educators Group Kobangdikal, Surabaya) - Warsono, Heribertus Yudho; Budiyanto, Budiyanto; Riduwan, Akhmad (Asia Pacific Journal of Management and Education (APJME), 2019)
Indonesia is the biggest archipelagic state with at least 17.506 islands, the two-thirds of the area (70%) consists of sea waters with a coastline of 81,000 km and is located between two continents, namely Australia and Asia, and is located between two oceans, the Pacific and the Indian. Through the UN Assembly in Montego Bay about the International Law of the Sea, the principles of the principle of the archipelagic state are included in the UNCLOS 1982 (United Nations Convention on the Law of the Sea) which influences the use of the EEZ for the benefit of national welfare and development. According to Law no. 34 of 2004 concerning the TNI, article 9, the task of the Indonesian Navy is to prepare and foster the power to uphold the sovereignty and integrity of the NKRI and protect national interests in the sea of national jurisdiction. Escorting the sea to such an extent is a heavy duty for the Navy, with such a daunting task, compared to the very limited number of naval organization of the Navy, it requires professional and qualified Navy soldiers who are able to work well, to achieve the objectives of the Indonesian Navy as mandated by law. The Navy in carrying out its role as a national defense force in the sea needs to build, shape and improve the quality of its human resources, this is done in an effort to obtain the ability and appearance of professional Navy soldiers shown by their performance, based on the soul of Sapta Marga, Sumpah Praskar and the Indonesian Navy's Trisila, in an integrated, continuous and balanced manner with provision of skills through education and assignments. The Development and Education Command of the Navy (Kobangdikal) is one of the Navy's educational institutions which is the Main Command of the Development of the Navy and is directly under the Chief of Staff by having the main task of carrying out the formal Navy and non-formal education needed to improve Navy soldiers, carry out the study and development of the doctrine of marine operations and the doctrine of amphibious operations at the level of tactics as well as the study and development of general support for sea operations and tactical amphibious operations.2 In order to organize the formal education of the Navy, Kobangdikal was carrying out first education (Dikma), formation education (Diktuk), general development education (Dikbangum), specialization development education (Dikbangspes), science and technology education (Dikiptek), transitional education (Dikalih) and education needed in order to improve the quality of Navy personnel. The Navy's educational philosophy, namely "Purwa Cendekia Wusana Color Dwi", implies that every Indonesian Navy Soldier is first formed and empowered as a Sapta Marga Warrior Soldier (Purwa Color Dwi) and subsequently as a Marine War Professional soldier who is skilled in carrying out assignment (Cendekia Wusana) as a National defense force. In more depth the philosophy means that faced with the demands and challenges of the tasks faced by the Indonesian Navy, then the education of mental and physical fitness is preferred and then competency education, which starts giving knowledge to be competent, training to be deft, assignments to be clever, experience to be smart and appreciate the tasks, functions and roles as the main force of defense of the Sea of the State so that the Indonesian Navy Soldiers are formed. In order to carry out these basic tasks various educational instruments are needed in the form of educational facilities and human resources quality in order to achieve the success of the Navy's main education task optimally. 1 Kepala Staf Angkatan Laut, Pola Pendidikan Prajurit TNI AL, Jakarta, 2008, p.3 2 Peraturan Kepala Staf Angkatan Laut: Perkasal/44/VII/2008 Tanggal 2 Juli 2008 tentang Pokok-Pokok Organisasi dan Prosedur Kobangdikal The main task of the Indonesian Navy's educational institutions cannot be separated from the existence of the Navy's education system which includes 8 (eight) aspects of education and 10 (ten) components of education. In 10 (ten) components of education, there are 2 (two) main aspects in the implementation of education, namely the availability of educators (Gadik) or in other terms called the military teacher (Gumil) and the students. Educators as one of the 10 components of education are the dominant factor in realizing educational goals and objectives. Educators are personnel who have mastered the knowledge, skills and technology in a particular subject that is taught for the next through an educational process, transferring knowledge, skills and technology to a student / student in the military / Indonesian Navy. Students are the general designation for Pasis, Cadets, Students, and so on according to the designation that applies in each educational institution. Integration between educators and students will take place continuously in accordance with the duration of education. Educator (Gadik) or military teacher (Gumil) in the Navy is a soldier / PNS Navy is the spearhead in the implementation of the teaching and learning process in Lemdik of Indonesian Navy, is one of the factors that greatly color the results of Kobangdikal students, both strata Officers, Bintara, or Tamtama. Educators (Gadik) are under the organizational structure of the Educator Teaching Group (Pokgadik) of the Indonesian Navy's Educational Development Command (Kobangdikal). Thus the position of the Educator (Gadik) is very important and strategic and is the main asset of the educational institution in supporting the basic tasks of the military. Human resources (HR) educators, is a necessity in an Educational Institution.